Thin-gauge automobile beam steel with tensile strength larger than 510 MPa and production method of thin-gauge automobile beam steel

Through reasonable component design and process technology, thin-specification steel for automotive beams with tensile strength greater than 510MPa was provided, which solved the problems of uneven solidification and poor welding performance caused by component design in the existing technology, and achieved high strength and high Toughness and good forming accuracy are suitable for automotive lightweight and safety needs.

CN119194274APending Publication Date: 2024-12-27BAOTOU IRON & STEEL (GROUP) CO LTD

Patent Information

Application Number
CN202411138071.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

While the existing steel for automobile beams improves tensile strength and thin specifications, there are problems such as uneven solidification of the initial blank shell, formation of carbide particles, poor welding performance and opposite-quality mechanical properties caused by component design, which is difficult to meet the lightweight and Security requirements.

Method used

Through reasonable component design and process technology, the chemical components are provided: C: 0.06-0.08%, Si: 0.03-0.10%, Mn: 0.80-1.00%, P: ≤ 0.018%, S: ≤ 0.005%, Al: 0.020- 0.045%, Nb: 0.012-0.022%, Ti: 0.025-0.037%, Ca: 0.0008-0.0020% of thin specifications of automotive beam steel, and smelting-continuous casting-slab heating-rolling-cooling-coiling Production method ensures that the microstructure of the steel is ferrite and dispersed carbides are precipitated, and the mechanical properties meet the yield strength of 450-480MPa, the tensile strength of 512-565MPa, and the elongation is 28-32%.

Benefits of technology

It realizes high strength, high toughness and good forming accuracy of steel, avoids component design problems in the existing technology, improves the overall performance of automotive beam steel, is suitable for industrial mass production, and meets the automotive lightweight and safety needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194274A_ABST
    Figure CN119194274A_ABST
Patent Text Reader

Abstract

The invention discloses steel for a thin-gauge automobile beam with the tensile strength larger than 510 MPa and a production method of the steel. The steel for the automobile beam comprises, by mass, 0.06%-0.08% of C, 0.03%-0.10% of Si, 0.80%-1.00% of Mn, smaller than or equal to 0.018% of P, smaller than or equal to 0.005% of S, 0.020%-0.045% of Alt, 0.012%-0.022% of Nb, 0.025%-0.037% of Ti, 0.0008%-0.0020% of Ca and the balance Fe and inevitable impurities. The steel for the thin automobile frame has the advantages of high strength, high toughness, high forming precision and the like, meets good matching of strength and forming performance in the performance aspect, is free of cracks in a cold bending test and has good cold machining performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgical material production, and specifically relates to a thin-gauge steel for automobile beams with a tensile strength greater than 510 MPa and a production method thereof. Background Art

[0002] With the rapid development of the automobile industry and the continuous increase in output, automobile steel has become the focus of major steel mills. In the case of large demand, energy is becoming increasingly scarce and environmental pressure is increasing, which has promoted the development of automobile technology to focus on energy saving, environmental protection and safety. The important trend of automobile steel development is to pursue the lightweight of the whole vehicle while ensuring safety performance, while reducing fuel consumption and reducing exhaust emissions. In order to achieve lightweighting of automobiles, the current automobile steel generally pursues thin specifications, high strength and high toughness. As an important load-bearing component of automobiles, automobile beam steel is mainly used to manufacture commercial automobile longitudinal beams and cross beams, and is increasingly developing in the direction of high strength, because the lower the strength level, the thicker the thickness used. Thin specifications and high strength not only ensure higher safety, but also help to lighten the automobile. The shape of automobile beams is relatively complex. In addition to strength and cold bending, they also require good stamping forming performance. Due to the development of modern metallurgical technology and the need for lightweighting of automobiles, thin specifications and high strength automobile beam steel have gradually become the preferred material for OEMs. As an entry-level product of high-strength steel, thin-gauge 510L not only meets users' demand for lightweighting, but also has excellent comprehensive mechanical properties. Currently, there is a large market demand for it and it has broad market prospects.

[0003] Patent document CN103451535A (hereinafter referred to as document 1) discloses a 510MPa grade hot-rolled strip steel for automobile beams and its production process, with a chemical composition ratio of C: 0.13-0.18%, Si: 0.30-0.50%, Mn: 0.75-1.15%, Ti: 0.008-0.025%, Alt: 0.02-0.06%, P≤0.025%, S≤0.008%, and N≤0.006%. The component design of this document 1 improves the strength by increasing the C and Si contents. First, when the C content is within this range, a peritectic reaction occurs, which will cause uneven solidification of the initial billet shell and lead to cracks in the continuous casting billet. Secondly, too high a carbon content will form coarse and brittle carbide particles, which is not conducive to plasticity and toughness. Too high a carbon content will also form a segregation band in the center of the steel plate, which is not conducive to bending performance and formability. At the same time, too high a carbon content increases the welding carbon equivalent and the welding crack sensitivity index, which is not conducive to welding processing. Too high a Si content not only reduces the welding performance, but also produces a large amount of red rust, resulting in poor surface quality.

[0004] Patent document CN102172622A (hereinafter referred to as document 2) discloses a production method of 510L black steel for automobile beams, the main chemical composition ratio is C: 0.06-0.14%, Si≤0.2%, Mn: 1.2-1.6%, Nb: 0.01-0.05%, Alt: 0.02-0.06%, P≤0.02%, S≤0.010%. Patent document CN113106332A (hereinafter referred to as document 3) discloses a low crack sensitivity 510L hot-rolled automobile structural steel strip and its production method, the main chemical composition ratio is C: 0.07-0.10%, Si≤0.2%, Mn: 1.3-1.5%, Ti: 0.02-0.04%, Als: 0.02-0.04%, P≤0.015%, S≤0.010%. The high Mn content in the composition design of the above references 2-3 is prone to segregation to form banded structure, making the mechanical properties of the material anisotropic and the cross-sectional shrinkage rate seriously reduced, which has an adverse effect on the subsequent processing and use of the steel. In addition, a high Mn content will deteriorate the welding performance of the steel. Summary of the invention

[0005] In view of the problems existing in the prior art, and in order to meet the market demand for automobile beam steel, further expand the market share, and enrich the product variety structure, the present invention adopts reasonable component design and process technology to develop a thin-gauge high-strength automobile beam steel with a tensile strength greater than 510MPa. The production results and user effects show that the various properties of the product meet the relevant technical requirements and user requirements. The present invention is specifically implemented by the following technical solutions.

[0006] In the first aspect, the present invention provides a thin-gauge automobile beam steel with a tensile strength greater than 510 MPa, the chemical composition of which is calculated by mass percentage: C: 0.06-0.08%, Si: 0.03-0.10%, Mn: 0.80-1.00%, P: ≤0.018%, S: ≤0.005%, Alt: 0.020-0.045%, Nb: 0.012-0.022%, Ti: 0.025-0.037%, Ca: 0.0008-0.0020%, and the rest is Fe and unavoidable inclusions.

[0007] In some embodiments, the chemical composition of the steel for automobile beams is, by mass percentage, C: 0.070%, Si: 0.05%, Mn: 0.80%, P: 0.018%, S: 0.004%, Alt: 0.045%, Nb: 0.016%, Ti: 0.026%, Ca: 0.0015%, and the rest is Fe and unavoidable inclusions.

[0008] In some embodiments, the chemical composition of the steel for automobile beams is, by mass percentage, C: 0.075%, Si: 0.08%, Mn: 0.88%, P: 0.016%, S: 0.003%, Alt: 0.040%, Nb: 0.020%, Ti: 0.030%, Ca: 0.0026%, and the rest is Fe and unavoidable inclusions.

[0009] In some embodiments, the chemical composition of the steel for automobile beams is, by mass percentage, C: 0.066%, Si: 0.10%, Mn: 0.90%, P: 0.015%, S: 0.003%, Alt: 0.030%, Nb: 0.022%, Ti: 0.027%, Ca: 0.0018%, and the rest is Fe and unavoidable inclusions.

[0010] In some embodiments, the chemical composition of the steel for automobile beams is, by mass percentage, C: 0.062%, Si: 0.06%, Mn: 0.93%, P: 0.017%, S: 0.002%, Alt: 0.035%, Nb: 0.015%, Ti: 0.033%, Ca: 0.0018%, and the rest is Fe and unavoidable inclusions.

[0011] In some embodiments, the chemical composition of the steel for automobile beams is, by mass percentage, C: 0.080%, Si: 0.07%, Mn: 1.00%, P: 0.018%, S: 0.002%, Alt: 0.025%, Nb: 0.014%, Ti: 0.032%, Ca: 0.0016%, and the rest is Fe and unavoidable inclusions.

[0012] In some embodiments, the thickness of the automobile beam steel is 2.0-6.0 mm.

[0013] In some embodiments, the microstructure of the steel for automobile beams is composed of ferrite and dispersed precipitated carbides, and the mechanical properties meet the following requirements: yield strength 450-480 MPa, tensile strength 512-565 MPa, and elongation 28-32%.

[0014] In a second aspect, the present invention provides a method for producing thin-gauge automobile beam steel with a tensile strength greater than 510 MPa, which comprises the following processes: smelting - continuous casting - slab heating - rolling - cooling - coiling; wherein:

[0015] The smelting-continuous casting process comprises: KR desulfurization-converter-LF refining-RH vacuum treatment-slab continuous casting-slow cooling, and the composition of the molten steel supplied to the casting machine is C: 0.06-0.08%, Si: 0.03-0.10%, Mn: 0.80-1.00%, P: ≤0.018%, S: ≤0.005%, Alt: 0.020-0.045%, Nb: 0.012-0.022%, Ti: 0.025-0.037%, Ca: 0.0008-0.0020%; wherein the superheat of the continuous casting process can be 26-31°C;

[0016] The slab heating process includes: sending the slab after surface cleaning into the heating furnace, strictly controlling the slab heating temperature, furnace time, soaking temperature, soaking time and furnace discharge temperature, the heating temperature is controlled at 1230±20°C, the furnace time is controlled at 160-270min, the soaking temperature is controlled at 1240±20°C, the soaking time is controlled at 25-50min, and the furnace discharge temperature is controlled at 1220±20°C;

[0017] The rolling process includes a rough rolling stage and a finishing rolling stage. The rough rolling stage adopts a 3+3 mode two-stand rolling mill for rough rolling, and the finishing stage adopts a 7-stand continuous variable crown rolling mill for finishing rolling. The finishing stage adopts speed increase rolling; the finishing rolling entrance thickness is 40mm, the starting rolling temperature of the finishing rolling is not less than 1030°C, and the final rolling temperature of the finishing rolling is 900±15°C;

[0018] The cooling process adopts laminar cooling equipment (cooling speed can be 25-28°C / s), and the cooling mode adopts the self-learning calculation result of the computer secondary system;

[0019] The coiling temperature is 600±15°C.

[0020] The present invention provides a thin-gauge automobile beam steel with a tensile strength greater than 510MPa through reasonable component design and combined with optimized production process parameters. The microstructure of the product is composed of ferrite and dispersed precipitated carbides, and the mechanical properties are as follows: yield strength 450-480MPa, tensile strength 512-565MPa, and elongation 28-32%. The product has good performance balance, and has the advantages of high strength, high toughness, high forming accuracy, etc., and meets the good matching of strength and forming performance in terms of performance. There is no crack in the cold bending test, and it has good cold working performance. At the same time, due to the improvement of the strength of the automobile beam steel strip of the present invention, the thickness of use is further reduced, and it becomes a lightweight material to replace low-strength grade steel. In addition, the production method of the product is simple and easy, suitable for industrial batch production, and all performances meet the requirements of relevant standards and user needs. Furthermore, in the composition design of the steel grade, low C and low Si are adopted, which can avoid the problems caused by increasing the C and Si contents in the above-mentioned document 1, and can also avoid the problems caused by the higher Mn content in the above-mentioned documents 2-3. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a microstructure photograph of the thin-gauge steel for automobile beams with a tensile strength greater than 510 MPa produced in Example 1. DETAILED DESCRIPTION

[0022] The present invention is described in detail below through specific examples. The examples are intended to help understand the present invention but are not intended to limit the present invention.

[0023] Example 1

[0024] The molten iron is pre-treated for desulfurization, and the top and bottom combined blown converter is used to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process, and scrap steel is added to the converter. The converter tapping temperature is 1647℃. Then the molten steel after converter smelting is subjected to LF refining outside the furnace, and the refining temperature is ≥1566℃. The LF refining outside the furnace is subjected to temperature measurement and composition fine-tuning. The chemical composition of the LF refining casting machine is shown in Table 1. The overheat of the slab continuous casting is 26℃, and then the slab is cleaned, slowly cooled, and the quality of the continuous casting is checked. The slab heating temperature is 1228℃, the heating time is 258min, and the heated slab is dephosphorized by high-pressure water. The width is set by a fixed width press, and 2-stand rough rolling and 7-stand CVC finishing rolling are used. The finishing rolling start temperature is 1033℃, the finishing rolling final rolling temperature is 905℃, and the finished product thickness is 3.0mm. Laminar cooling uses front dispersion cooling, cooling rate is 26℃ / s, and the temperature of the steel strip is reduced to 590℃ for coiling. Finally, the product performance test is carried out, as shown in Table 2 below. Figure 1 As shown, the microstructure diagram of the hot-rolled steel for beams obtained in this embodiment is shown, and it can be seen that the microstructure is ferrite and dispersed precipitated carbides.

[0025] Example 2

[0026] The molten iron is pre-treated for desulfurization, and the top and bottom combined blown converter is used to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process, scrap steel is added to the converter, and the converter tapping temperature is 1653℃. Then the molten steel after converter smelting is subjected to LF refining outside the furnace, and the refining temperature is ≥1564℃. The LF refining outside the furnace is subjected to temperature measurement and composition fine-tuning. The chemical composition of the LF refining casting machine is shown in Table 1. The overheat of the slab continuous casting is 28℃, and then the slab is cleaned, slowly cooled, and the quality of the continuous casting is checked. The slab heating temperature is 1223℃, and the heating time is 265min. The heated slab is dephosphorized by high-pressure water. The width is set by a fixed width press, and 2-stand rough rolling and 7-stand CVC finishing rolling are used. The finishing rolling start temperature is 1036℃, the finishing rolling final temperature is 893℃, and the finished product thickness is 4.0mm. Laminar cooling adopts front dispersion cooling with a cooling rate of 28°C / s. The temperature of the steel strip is reduced to 593°C for coiling, and finally the product performance is tested, as shown in Table 2 below.

[0027] Example 3

[0028] The molten iron is pre-treated for desulfurization, and the top and bottom combined blown converter is used to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process, scrap steel is added to the converter, and the converter tapping temperature is 1645℃. Then the molten steel after converter smelting is subjected to LF refining outside the furnace, and the refining temperature is ≥1560℃. The LF refining outside the furnace is subjected to temperature measurement and composition fine-tuning. The chemical composition of the LF refining casting machine is shown in Table 1. The overheat of the slab continuous casting is 27℃, and then the slab is cleaned, slowly cooled, and the quality of the continuous casting is checked. The slab heating temperature is 1225℃, and the heating time is 258min. The heated slab is dephosphorized by high-pressure water. The width is set by a fixed width press, and 2-stand rough rolling and 7-stand CVC finishing rolling are used. The finishing rolling start temperature is 1031℃, the finishing rolling final temperature is 900℃, and the finished product thickness is 5.0mm. Laminar cooling adopts front dispersion cooling with a cooling rate of 27°C / s. The temperature of the steel strip is reduced to 608°C for coiling, and finally the product performance is tested, as shown in Table 2 below.

[0029] Example 4

[0030] The molten iron is pre-treated for desulfurization, and the top and bottom combined blown converter is used to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process, scrap steel is added to the converter, and the converter tapping temperature is 1641℃. Then the molten steel after converter smelting is subjected to LF refining outside the furnace, and the refining temperature is ≥1562℃. The LF refining outside the furnace is subjected to temperature measurement and composition fine-tuning. The chemical composition of the LF refining casting machine is shown in Table 1. The overheat of the slab continuous casting is 32℃, and then the slab is cleaned, slowly cooled, and the quality of the continuous casting is checked. The slab heating temperature is 1220℃, the heating time is 263min, and the heated slab is dephosphorized by high-pressure water. The width is set by a fixed width press, and 2-stand rough rolling and 7-stand CVC finishing rolling are used. The finishing rolling start temperature is 1030℃, the finishing rolling final rolling temperature is 896℃, and the finished product thickness is 6.0mm. Laminar cooling adopts front dispersion cooling with a cooling rate of 26°C / s. The temperature of the steel strip is reduced to 602°C for coiling, and finally the product performance is tested, as shown in Table 2 below.

[0031] Example 5

[0032] The molten iron is pre-treated for desulfurization, and the top and bottom combined blown converter is used to decarbonize and dephosphorize the molten iron to obtain molten steel. Argon is blown throughout the converter smelting process, and scrap steel is added to the converter. The converter tapping temperature is 1652℃. Then the molten steel after converter smelting is subjected to LF refining outside the furnace, and the refining temperature is ≥1563℃. The LF refining outside the furnace is subjected to temperature measurement and composition fine-tuning. The chemical composition of the LF refining casting machine is shown in Table 1. The overheat of the slab continuous casting is 31℃, and then the slab is cleaned, slowly cooled, and the quality of the continuous casting is checked. The slab heating temperature is 1228℃, the heating time is 257min, and the heated slab is dephosphorized by high-pressure water. The width is set by a fixed width press, and 2-stand rough rolling and 7-stand CVC finishing rolling are used. The finishing rolling start temperature is 1032℃, the finishing rolling final temperature is 902℃, and the finished product thickness is 2.0mm. Laminar cooling adopts front dispersion cooling with a cooling rate of 25°C / s. The temperature of the steel strip is reduced to 596°C for coiling, and finally the product performance is tested, as shown in Table 2 below.

[0033] Comparative Example 1

[0034] The production method is the same as that shown in Example 1, except that the chemical composition of the LF refining feed casting machine is different from that used in Example 1, as shown in Table 1. Finally, the product performance test is carried out, as shown in Table 2.

[0035] Comparative Example 2

[0036] The production method is the same as that shown in Example 5, except that the chemical composition of the LF refining casting machine is different from that used in Example 5, as shown in Table 1. Finally, the product performance test is carried out, as shown in Table 2.

[0037] Comparative Examples 3-4

[0038] The production method of Comparative Examples 3-4 is the same as that of Example 1, except that the coiling temperature is different from that of Example 1, specifically, the coiling temperature of Comparative Example 3 is 550° C., and the coiling temperature of Comparative Example 4 is 660° C. Finally, the product performance is tested, as shown in Table 2 below.

[0039] Table 1: Chemical composition (wt%) of Examples 1 to 5 and Comparative Examples 1 to 4 of the present invention

[0040] Example C Si Mn P S Alt Nb Ti Ca 1 0.070 0.05 0.80 0.018 0.004 0.045 0.016 0.026 0.0015 2 0.075 0.08 0.88 0.016 0.003 0.040 0.020 0.030 0.0026 3 0.066 0.10 0.90 0.015 0.003 0.030 0.022 0.027 0.0018 4 0.062 0.06 0.93 0.017 0.002 0.035 0.015 0.033 0.0018 5 0.080 0.07 1.00 0.018 0.002 0.025 0.014 0.032 0.0016 Comparative Example 1 0.070 0.05 0.50 0.018 0.004 0.045 0.016 0.020 0.0015 Comparative Example 2 0.080 0.07 1.28 0.018 0.002 0.025 0.024 0.032 0.0016 Comparative Example 3 0.070 0.05 0.80 0.018 0.004 0.045 0.016 0.026 0.0015 Comparative Example 4 0.070 0.05 0.80 0.018 0.004 0.045 0.016 0.026 0.0015

[0041] Table 2: Mechanical properties of the steel coils of Examples 1 to 5 of the present invention and Comparative Examples 1 to 4

[0042]

[0043] It can be seen from the contents recorded in Tables 1 and 2 above that the mechanical properties of the thin-gauge hot-rolled automobile beam steel provided by the present invention can meet the following requirements: yield strength ≥355MPa, tensile strength 510-630MPa, elongation ≥24%, preferably: yield strength 467-518MPa, tensile strength 539-581MPa, elongation 26-30%. The product has good performance balance, and has the advantages of high strength, high toughness, high forming precision, etc. In terms of performance, it meets the good matching of strength and forming performance, and there is no crack in the cold bending test, and it has good cold processing performance. In addition, the production method is simple and easy, suitable for industrial mass production, and it meets the demand for automobile wheel steel very well, and all performances meet the requirements of relevant standards and user needs. According to the test results of Comparative Examples 1-2, when the chemical composition of the product cannot meet the requirements of the present invention, the mechanical properties of the product will be unqualified. For example, when the content of Mn and Ti in Comparative Example 1 is lower than the standard requirements, the product strength is lower than the standard requirements and cannot meet the needs of users; when the content of Mn and Nb in Comparative Example 2 is higher than the standard requirements, the product strength is high and the elongation is low, and cracking occurs in the bending test, and the cold processing formability is poor during the later use. According to the results of Comparative Examples 3-4, when the chemical composition of the product meets the requirements of the present invention, but the production process does not meet the requirements of the present invention, for example, when the coiling temperature is higher or lower than the set value, the obtained product performance will also fail to meet the requirements. In Comparative Example 3, the low coiling temperature leads to high strength and cracking in the bending test, which cannot meet the needs of users; in Comparative Example 4, the high coiling temperature will cause the product strength to be low, resulting in insufficient load-bearing capacity during subsequent use.

[0044] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A thin-gauge automobile beam steel with a tensile strength greater than 510 MPa, whose chemical composition is as follows by mass percentage: C: 0.06-0.08%, Si: 0.03-0.10%, Mn: 0.80-1.00%, P: ≤0.018%, S: ≤0.005%, Alt: 0.020-0.045%, Nb: 0.012-0.022%, Ti: 0.025-0.037%, Ca: 0.0008-0.0020%, and the rest is Fe and unavoidable inclusions.

2. The steel for automobile beams according to claim 1, wherein the chemical composition, by mass percentage, is: C: 0.070%, Si: 0.05%, Mn: 0.80%, P: 0.018%, S: 0.004%, Alt: 0.045%, Nb: 0.016%, Ti: 0.026%, Ca: 0.0015%, and the remainder is Fe and unavoidable inclusions.

3. The steel for automobile beams according to claim 1, wherein the chemical composition, by mass percentage, is: C: 0.075%, Si: 0.08%, Mn: 0.88%, P: 0.016%, S: 0.003%, Alt: 0.040%, Nb: 0.020%, Ti: 0.030%, Ca: 0.0026%, and the remainder is Fe and unavoidable inclusions.

4. The steel for automobile beams according to claim 1, wherein the chemical composition, by mass percentage, is: C: 0.066%, Si: 0.10%, Mn: 0.90%, P: 0.015%, S: 0.003%, Alt: 0.030%, Nb: 0.022%, Ti: 0.027%, Ca: 0.0018%, and the remainder is Fe and unavoidable inclusions.

5. The steel for automobile beams according to claim 1, wherein the chemical composition, by mass percentage, is: C: 0.062%, Si: 0.06%, Mn: 0.93%, P: 0.017%, S: 0.002%, Alt: 0.035%, Nb: 0.015%, Ti: 0.033%, Ca: 0.0018%, and the remainder is Fe and unavoidable inclusions.

6. The steel for automobile beams according to claim 1, wherein the chemical composition, by mass percentage, is: C: 0.080%, Si: 0.07%, Mn: 1.00%, P: 0.018%, S: 0.002%, Alt: 0.025%, Nb: 0.014%, Ti: 0.032%, Ca: 0.0016%, and the remainder is Fe and unavoidable inclusions.

7. The steel for automobile beam according to claim 1, having a thickness of 2.0-6.0 mm.

8. The steel for automobile beams according to any one of claims 1 to 7, wherein the microstructure thereof is composed of ferrite and dispersed precipitated carbides, and the mechanical properties thereof meet the following requirements: yield strength 450-480 MPa, tensile strength 512-565 MPa, and elongation 28-32%.

9. The method for producing the automobile beam steel according to any one of claims 1 to 8, comprising the following process: Smelting - continuous casting - slab heating - rolling - cooling - coiling; among which: The smelting-continuous casting process comprises: KR desulfurization-converter-LF refining-RH vacuum treatment-slab continuous casting-slow cooling, and the composition of the molten steel supplied to the casting machine is C: 0.06-0.08%, Si: 0.03-0.10%, Mn: 0.80-1.00%, P: ≤0.018%, S: ≤0.005%, Alt: 0.020-0.045%, Nb: 0.012-0.022%, Ti: 0.025-0.037%, Ca: 0.0008-0.0020%; The slab heating process includes: sending the slab after surface cleaning into the heating furnace, strictly controlling the slab heating temperature, furnace time, soaking temperature, soaking time and furnace discharge temperature, the heating temperature is controlled at 1230±20°C, the furnace time is controlled at 160-270min, the soaking temperature is controlled at 1240±20°C, the soaking time is controlled at 25-50min, and the furnace discharge temperature is controlled at 1220±20°C; The rolling process includes a rough rolling stage and a finishing rolling stage. The rough rolling stage adopts a 3+3 mode two-stand rolling mill for rough rolling, and the finishing stage adopts a 7-stand continuous variable crown rolling mill for finishing rolling. The finishing stage adopts speed increase rolling; the finishing rolling entrance thickness is 40mm, the starting rolling temperature of the finishing rolling is not less than 1030°C, and the final rolling temperature of the finishing rolling is 900±15°C; The cooling process adopts laminar cooling equipment, and the cooling mode adopts the self-learning calculation result of the computer secondary system; The coiling temperature is 600±15°C.

Citation Information

Patent Citations

  • High-strength antifatigue steel products and method for manufacturing same

    CN101139685A

  • Low-cost automobile girder hot rolled steel plate and production method

    CN104694824A

  • Automobile beam steel with tensile strength of 550MPa and preparation method for automobile beam steel

    CN104805358A

  • 420 MPa grade cold rolled low-alloy high-strength steel for automobile and production method thereof

    CN111394643A

  • Manufacturing method for producing hot-rolled 510L automobile beam steel based on CSP process

    CN115369307A

Cited By

  • Ti microalloyed thin-gauge automobile compartment steel with yield strength larger than 355MPa and production method of Ti microalloyed thin-gauge automobile compartment steel

    CN119876776A